Plasma human growth cytokines in children with vasovagal syncope - Wang, Yuanyuan; Wang, Yaru; He, Bing; Tao, Chunyan; Han, Zhenhui; Liu, Ping; Wang, Yuli; Tang, Chaoshu; Liu, Xueqin; Du, Junbao; Jin, Hongfang (Frontiers in Cardiovascular Medicine, 2022)
Purpose The study was designed to investigate the profile of plasma human growth cytokines in pediatric vasovagal syncope (VVS). Materials and methods In the discovery set of the study, plasma human growth cytokines were measured using a Quantiboby Human Growth Factor Array in 24 VVS children and 12 healthy controls. Scatter and principal component analysis (PCA) diagrams were used to describe the samples, an unsupervised hierarchical clustering analysis was used to categorize the samples. Subsequently, the cytokines obtained from the screening assays were verified with a suspension cytokine array in the validation set of the study including 53 VVS children and 24 controls. Finally, the factors associated with pediatric VVS and the predictive value for the diagnosis of VVS were determined. Results In the discovery study, the differential protein screening revealed that the plasma hepatocyte growth factor (HGF), transforming growth factor b1 (TGF-b1), insulin-like growth factor binding protein (IGFBP)-4, and IGFBP-1 in children suffering from VVS were higher than those of the controls (all adjust P- value < 0.05). However, the plasma IGFBP-6, epidermal growth factor (EGF), and IGFBP-3 in pediatric VVS were lower than those of the controls (all adjust P- value < 0.01). Meanwhile, the changes of 7 differential proteins were analyzed by volcano plot. Unsupervised hierarchical cluster analysis demonstrated that patients in the VVS group could be successfully distinguished from controls based on the plasma level of seven differential proteins. Further validation experiments showed that VVS patients had significantly higher plasma concentrations of HGF, IGFBP-1, and IGFBP-6, but lower plasma concentrations of EGF and IGFBP-3 than controls. The logistics regression model showed that increased plasma concentration of HGF and IGFBP-1 and decreased plasma concentration of EGF were correlated with the development of pediatric VVS. ROC curve analysis showed that the abovementioned 3 proteins were useful for assisting the diagnosis of VVS. Conclusion Plasma human growth cytokine profiling changed in pediatric VVS. Elevated plasma concentrations of HGF and IGFBP-1, and decreased EGF were associated factors in the development of pediatric VVS. The abovementioned three proteins are helpful for the diagnosis of pediatric VVS.